Measurement of ear length in neonates, infants and preschool children in Taiwan - Chou, Chun-Te; Tseng, Ya-Chun; Tsai, Fuu-Jen; Lin, Cheng-Chieh; Liu, Chiu-Shong; Peng, Ching-Tien; Tsai, Chang-Hai (Acta paediatrica Taiwanica = Taiwan er ke yi xue hui za zhi, 2002)
Ear length is important in the evaluation of congenital anomaly syndrome, such as small ear in Down syndrome. In this research, 4,416 normal Chinese children in Taiwan were enrolled into our study. The sample of 284 full term neonates, 2,742 infants and children aged from one month to three years, and 1,420 preschool children were measured for ear length. We placed a ruler along the greatest vertical axis of the right ear We calculated the mean value and standard deviation of the ear length in normal Chinese neonates, infants and preschool children in Taiwan. No significant sex differences were observed. Twenty patients with Down syndrome were also measured. Compared with the previous study, there was no significant difference between the ear length of Chinese children and that of Caucasian children. The ear length of patients with Down syndrome was indeed smaller than that of the normal children. Due to the correlation of reduced ear length and congenital anomaly, we should set up our own data about the growth of the ear length. Thus we can provide an additional clue to diagnose the congenital anomaly syndromes.